Buying And Selling “Ijon”: Perspective of the Hadith - Maidin, Muhammad Sabir; Khalik, Subehan (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
Ijon is a form of buying and selling transactions that are commonly carried out by the community and is a form of buying and selling which causes differences of opinion. This study attempts to analyze in depth the existence of bonded trading by examining hadith. It was found that the hadiths that talk about the practice of bondage are of valid quality and become a legal basis that is strong enough to abolish the practice of buying and selling debt bondage. By using the research method of takhrij hadith in lafzi and thematically, the related hadiths are of valid quality. Thus, the basic argument for declaring the invalidity of bonded trading is very strong